Supplementation of Red Dragon Fruit Peel Extract (Hylocereus polyrhizus) in CEP-2 Extender on the Qualities of Limousin Bull Chilled Semen. Issue 1 (April 2020) - Wahjuningsih, S; Yekti, A P A; Grace, A; Amalia
Abstract: The purpose of this study was to determine the effect of red dragon fruit peel extract (RDFPE) supplementation in CEP-2 extender to the qualities of Limousin semen during 3-5 °C storage. The semen was collected by using artificial vagina twice a week for 5 weeks. The treatments in this research were RDFPE supplementation at 0%, 1%, 3% and 5% on the CEP-2 base extender and the observed variables include semen motility and viability. The results showed that the addition of RDFPE in CEP-2 extender gave a significant effect (P<0.05) to the semen motility and viability. Supplementation of RDFPE at 3% showed better motility and viability than 0, 1 and 5%. The study concludes that the addition of 3% RDFPE was the best treatment in maintaining the quality of Limousin bull semen at cold temperature.